Penggunaan Buku Ajar Nihongo Kirakira I pada Pembelajaran Bahasa Jepang di SMA Kesatrian I Semarang - Nita Kusumawati; Lispridona Diner (JLA (Jurnal Lingua Applicata), 2020)
Nihongo Kirakira I is a textbook published by The Japan Foundation and compiled by following the Content Competencies and Basic Competencies of the 2013 curriculum for secondary education. This book has fulfilled the requirements of the Ministry of Education and Culture to answer the needs of basic level Japanese language learners, equivalent to the level 5 JLPT (Japanese Language Proficiency Test). Preliminary studies show that there are positive responses regarding to this book from students in Kesatrian 1 High School Semarang. This study aims to investigate the further responses about Japanese language learning by using Nihongo Kirakira I. This research was conducted by using quantitative descriptive methods, involving 72 respondents in Kesatrian High School 1. The data were obtained through open and closed questionnaires, then analyzed by using percentage descriptive techniques. The result shows that 42 respondents (58%) gave "good" response and 30 respondents (42%) gave "not good" response. Poor responses are caused by respondents’ difficulty in pronouncing Japanese vocabulary and in reading hiragana and katakana letters. In general, respondents thought that learning Japanese using Nihongo Kirakira I is adequate.